2011
DOI: 10.1016/j.metabol.2010.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Management of type 2 diabetes: evolving strategies for the treatment of patients with type 2 diabetes

Abstract: The prevalence of type 2 diabetes continues to increase at an alarming rate around the world, with even more people being affected by prediabetes. Although the pathogenesis and long-term complications of type 2 diabetes are fairly well known, its treatment has remained challenging, with only half of the patients achieving the recommended hemoglobin A1c target. This narrative review explores the pathogenetic rationale for the treatment of type 2 diabetes, with the view of fostering better understanding of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
215
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 294 publications
(221 citation statements)
references
References 192 publications
(234 reference statements)
0
215
0
6
Order By: Relevance
“…Control of postprandial hyperglycemia in diabetes is of great importance due to its close relation to the risk of micro and macro-vascular complications and death (Nyenwe et al, 2011). In the present investigation, experimental evaluation of the hypoglycemic potentials of O. sanctum has shown that the higher dose of extract (250 mg/kg body wt.)…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Control of postprandial hyperglycemia in diabetes is of great importance due to its close relation to the risk of micro and macro-vascular complications and death (Nyenwe et al, 2011). In the present investigation, experimental evaluation of the hypoglycemic potentials of O. sanctum has shown that the higher dose of extract (250 mg/kg body wt.)…”
Section: Resultsmentioning
confidence: 55%
“…With increasing incidence and mortality from its complications, prompt and adequate glycemic control in diabetes is paramount if management can meaningfully improve the quality of life and increase life expectancy (Nyenwe et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Control of postprandial hyperglycemia in diabetes is of great importance due to its close relation to the risk of micro and macro-vascular complications and death (Nyenwe et al, 2011). In this study, experimental evaluation of the hypoglycemic potentials of C. roseus and O. ficus-indica has shown that the higher dose of extract (250 mg/kg body wt.)…”
Section: The Results Indicated Potential Antidiabetic Action Of C Romentioning
confidence: 83%
“…Diabetes mellitus (DM) is the third leading disease, after heart attack and cancer affecting almost every organ in the human body (Nyenwe et al, 2011) and is also called silent killer. This is a metabolic disorder of multiple etiologies characterized by absolute or relative deficiency of insulin secretion with or without varying degree of insulin resistance (Lin and Sun, 2010;Nyenwe et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation